Tin oxide ceramic material as well as preparation method and application thereof

Through multi-step process processing, high-density, low-resistance, and fine grain tin oxide ceramic materials were prepared, which solved the problems of existing materials' density and resistivity, and was suitable for the preparation of high-quality films.

CN119613101APending Publication Date: 2025-03-14FUJIAN ACETRON NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510054694.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing tin oxide ceramic materials are difficult to be dense, have high body resistivity and are too large in size, which affects their performance in film performance in magnetron sputtering.

Method used

By wet ball milling, spray drying, pressing and sintering solid raw materials such as tin oxide, conductive doped oxide, sintering aid, and gallium oxide, wet ball milling, spray drying, multiple pressing and multiple sintering, tin oxide ceramic materials with high relative density, low volume resistivity and fine grain size were prepared.

Benefits of technology

The prepared tin oxide ceramic material has a high relative density (98.1 to 99.5%), a low volume resistivity (28 to 61 mΩ·cm) and a small grain size (1 to 5 μm). It is suitable as a target for magnetron sputtering, and can improve the light transmittance and electron mobility of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613101A_ABST
    Figure CN119613101A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of ceramic preparation, and particularly relates to a tin oxide ceramic material and a preparation method and application thereof. According to the invention, oxygen vacancies are introduced into the conductive doped oxide, so that the conductivity of tin oxide is greatly improved; the sintering aid promotes liquid-phase sintering of the biscuit in the sintering process, so that the problem of sintering difficulty caused by volatilization of tin oxide at a high temperature of 1200 DEG C is solved, particle rearrangement and mass transfer processes are greatly promoted, and sintering densification of tin oxide is promoted; due to the introduction of gallium oxide, not only is pinning at the tin oxide grain boundary to prevent grain growth and obtain uniform and fine grain size, but also the conductivity of the ceramic material is further improved. The tin oxide ceramic material obtained by the invention has the characteristics of high density, low resistivity and uniform and fine crystal grains. Meanwhile, the preparation process is simple and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic preparation, and in particular relates to a tin oxide ceramic material and a preparation method and application thereof. Background Art

[0002] Transparent conductive oxide (TCO) films have high transmittance (>85%) for visible light, low resistivity (up to 10 -3 ~10 -4 Ω·cm) and other excellent photoelectric properties, so it is widely used in flat panel displays, solar cells and biosensors. Among them, the most used is tin-doped indium oxide (ITO) film. Although ITO film is widely used in many fields, due to its high cost (small natural reserves of indium), it is urgently needed to replace it with conductive films without or with less indium. Among them, tin oxide-based materials are relatively cheap, combined with their high transmittance, tin oxide-based materials can be used as excellent substitutes for indium oxide-based TCO.

[0003] High-density tin oxide ceramic material is a wide bandgap semiconductor material with a direct bandgap. It has the characteristics of good stability and high mobility. It is a potential material to replace ITO target materials. However, traditional tin oxide targets have too low density. During magnetron sputtering, the transmittance, mobility and other properties of the product film are reduced. At the same time, it also affects the magnetron sputtering process. Therefore, it is of great significance to develop tin oxide targets with excellent performance.

[0004] The prior art discloses that ZnO doping is used as a sintering aid to increase the density of pure SnO2 targets, and the relative density of the targets reaches more than 97.6%, but the bulk resistivity of the obtained targets is as high as 49Ω·cm. The prior art also discloses that tantalum tin oxide targets with a relative density of more than 97.9% are obtained by introducing tantalum and adjusting process parameters, but the average grain size of the target cross section is greater than 20um, which is not conducive to subsequent sputtering to obtain high-quality thin films. The prior art also discloses that the densification problem is solved by co-doping with gallium and zinc, but the resistivity of the target prepared is relatively high, and the patent does not study the effect of doping on grain size.

[0005] Therefore, there is an urgent need to solve the problems of existing tin oxide ceramic materials such as difficulty in densification, high bulk resistivity and excessively large grain size. Summary of the invention

[0006] The object of the present invention is to provide a tin oxide ceramic material and a preparation method and application thereof. The tin oxide ceramic material prepared by the method provided by the present invention is dense, has low bulk resistance and small grain size.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a tin oxide ceramic material, comprising the following steps:

[0009] Mixing solid raw materials, dispersants, defoamers and binders, and performing wet ball milling to obtain slurry; the solid raw materials include tin oxide, conductive doped oxides, sintering aids and gallium oxide;

[0010] The slurry is spray-dried to obtain a powder;

[0011] The powder is subjected to a first pressing and a second pressing in sequence to obtain a ceramic green body;

[0012] The ceramic green body is subjected to a first sintering, a second sintering and a third sintering in sequence to obtain the tin oxide ceramic material.

[0013] Preferably, the conductive doped oxide includes one or more of tantalum pentoxide, antimony trioxide, tungsten trioxide, molybdenum trioxide and vanadium pentoxide;

[0014] The sintering aid includes one or more of zinc oxide, copper oxide, silicon dioxide and manganese dioxide;

[0015] The mass ratio of the tin oxide to the conductive doped oxide is 91-99:0.5-4;

[0016] The mass ratio of tin oxide to sintering aid is 91-99:0.25-3;

[0017] The mass ratio of tin oxide to gallium oxide is 91-99:0.25-2.

[0018] Preferably, the dispersant includes one or more of polyacrylamide, styrene-maleic anhydride copolymer, polyethylene glycol, polyvinyl pyrrolidone, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol and cellulose derivatives; the cellulose derivatives include hydroxypropyl methylcellulose and / or carboxymethyl cellulose;

[0019] The defoaming agent includes one or more of polydimethylsiloxane, ethylene oxide-propylene oxide copolymer, diethylhexanol, isooctyl alcohol, isopentanol, diisobutyl carbinol, distearyl ethylenediamine and tributyl phosphate;

[0020] The binder includes one or more of cellulose, polyvinyl alcohol, polyvinyl acetate, polyvinyl ketone and polyacrylic acid.

[0021] Preferably, the mass of the dispersant is 0.5-2% of the mass of the solid raw material;

[0022] The mass of the defoamer is 0.05-0.1% of the mass of the solid raw material;

[0023] The mass of the binder is 1-4% of the mass of the solid raw material.

[0024] Preferably, the dispersion medium used in the wet ball milling is water, and the mass of the water is 70-100% of the mass of the solid raw material;

[0025] The rotation speed of the wet ball mill is 150-350 rpm;

[0026] The grinding balls used in the wet ball mill are zirconia grinding balls, which include grinding balls with a diameter of 6 mm, grinding balls with a diameter of 4 mm, and grinding balls with a diameter of 2 mm, and the mass ratio of the grinding balls with a diameter of 6 mm, the grinding balls with a diameter of 4 mm, and the grinding balls with a diameter of 2 mm is 1:3:6;

[0027] The ball-to-material ratio of the wet ball milling is 1 to 6:1.

[0028] Preferably, the inlet temperature of the spray drying is 210-240°C, and the outlet temperature is 100-120°C.

[0029] Preferably, the first pressing pressure is 20-70 MPa, and the holding time is 2-5 min;

[0030] The second pressing pressure is 200-300 MPa, and the holding time is 5-15 min.

[0031] Preferably, the first sintering temperature is 500-700°C, and the holding time is 2-4h;

[0032] The second sintering temperature is 900-1100°C, and the holding time is 2-10h;

[0033] The temperature of the third sintering is 1300-1600° C., and the holding time is 12-48 hours;

[0034] The second sintering and the third sintering are both performed under oxygen conditions.

[0035] The present invention also provides a tin oxide ceramic material prepared by the preparation method described in the above technical solution, wherein the relative density of the tin oxide ceramic material is 98.1-99.5%, the volume resistivity is 28-61 mΩ·cm, and the average grain size is 1-5 μm.

[0036] The present invention also provides the use of the tin oxide ceramic material described in the above technical solution as a target material.

[0037] The invention provides a method for preparing a tin oxide ceramic material, comprising the following steps: mixing a solid raw material, a dispersant, a defoaming agent and a binder, and performing wet ball milling to obtain a slurry; the solid raw material comprises tin oxide, a conductive doped oxide, a sintering aid and gallium oxide; spray drying the slurry to obtain a powder; sequentially performing a first pressing and a second pressing on the powder to obtain a ceramic blank; sequentially performing a first sintering, a second sintering and a third sintering on the ceramic blank to obtain the tin oxide ceramic material.

[0038] In the present invention, the conductive doped oxide greatly improves the conductivity of tin oxide by introducing oxygen vacancies; the sintering aid promotes liquid phase sintering of the green blank during the sintering process, solves the sintering difficulty caused by the high temperature volatilization of tin oxide at 1200°C, greatly promotes the particle rearrangement and mass transfer process, and promotes the sintering densification of tin oxide; the introduction of gallium oxide not only pins the tin oxide grain boundaries to hinder the growth of grains, obtains a uniform and fine grain size, but also further improves the conductivity of the ceramic material. The tin oxide ceramic material obtained by the present invention has the characteristics of high density, low resistivity, and uniform and fine grains. At the same time, the preparation process of the present invention is simple and suitable for industrial production.

[0039] The present invention also provides the use of the tin oxide ceramic material described in the above technical solution as a target material. The tin oxide film prepared by using the tin oxide ceramic material provided by the present invention as a target material has good light transmittance and high electron mobility, and because the ceramic material has a small grain size, the target material has better strength and faster sputtering rate. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a cross-sectional SEM image of the tin oxide ceramic material obtained in Example 1;

[0041] Figure 2 1 is the XRD diagram of the tin oxide raw material and the obtained tin oxide ceramic material in Example 1. DETAILED DESCRIPTION

[0042] The present invention provides a method for preparing a tin oxide ceramic material, comprising the following steps:

[0043] Mixing solid raw materials, dispersants, defoamers and binders, and performing wet ball milling to obtain slurry; the solid raw materials include tin oxide, conductive doped oxides, sintering aids and gallium oxide;

[0044] The slurry is spray-dried to obtain a powder;

[0045] The powder is subjected to a first pressing and a second pressing in sequence to obtain a ceramic green body;

[0046] The ceramic green body is subjected to a first sintering, a second sintering and a third sintering in sequence to obtain the tin oxide ceramic material.

[0047] The invention mixes solid raw materials, dispersants, defoamers and binders, and performs wet ball milling to obtain slurry; the solid raw materials include tin oxide, conductive doped oxide, sintering aid and gallium oxide.

[0048] In the present invention, the conductive doped oxide preferably includes one or more of tantalum pentoxide, antimony trioxide, tungsten trioxide, molybdenum trioxide and vanadium pentoxide. In the present invention, the sintering aid preferably includes one or more of zinc oxide, copper oxide, silicon dioxide and manganese dioxide. In the present invention, the mass ratio of tin oxide to conductive doped oxide is preferably 91-99:0.5-4; the mass ratio of tin oxide to sintering aid is preferably 91-99:0.25-3; the mass ratio of tin oxide to gallium oxide is preferably 91-99:0.25-2. In the present invention, the purity of each raw material in the solid raw material is preferably ≥99.99%. In the present invention, the addition amount of each doped oxide needs to be strictly controlled. Excessive doping will lead to a decrease in the light transmittance of the obtained thin film during subsequent coating applications.

[0049] In the present invention, the dispersant preferably includes one or more of polyacrylamide, styrene-maleic anhydride copolymer, polyethylene glycol, polyvinyl pyrrolidone, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol and cellulose derivatives; the cellulose derivatives preferably include hydroxypropyl methylcellulose and / or carboxymethyl cellulose. In the present invention, the defoamer preferably includes one or more of polydimethylsiloxane, ethylene oxide-propylene oxide copolymer, diethylhexanol, isooctyl alcohol, isopentanol, diisobutyl carbinol, distearyl ethylenediamine and tributyl phosphate. In the present invention, the binder preferably includes one or more of cellulose, polyvinyl alcohol, polyvinyl acetate, polyvinyl ketone and polyacrylic acid. In the present invention, the mass of the dispersant is preferably 0.5-2% of the mass of the solid raw material; the mass of the defoamer is preferably 0.05-0.1% of the mass of the solid raw material; the mass of the binder is preferably 1-4% of the mass of the solid raw material.

[0050] In the present invention, the dispersion medium used in the wet ball milling is preferably water, and more preferably pure water; the mass of the water is preferably 70-100% of the mass of the solid raw material; the rotation speed of the wet ball milling is preferably 150-350rpm; the grinding balls used in the wet ball milling are preferably zirconia grinding balls, and the zirconia grinding balls preferably include grinding balls with a diameter of 6mm, grinding balls with a diameter of 4mm and grinding balls with a diameter of 2mm, and the mass ratio of the grinding balls with a diameter of 6mm, the grinding balls with a diameter of 4mm and the grinding balls with a diameter of 2mm is preferably 1:3:6; the ball-to-material ratio of the wet ball milling is preferably 1-6:1, and more preferably 2-5:1.

[0051] In the present invention, the wet ball milling process preferably includes: mixing the solid raw material, dispersant, defoaming agent and water for a first wet ball milling, and then adding a binder for a second wet ball milling; the time for the first wet ball milling is preferably 4 to 24 hours, and the time for the second wet ball milling is preferably 0.5 to 2 hours.

[0052] In the present invention, it is preferred to add the binder last, mainly to ensure uniform mixing: if the binder is added at the beginning, the binder may wrap part of the particles, hinder the mutual collision and mixing between the ceramic particles, and cause uneven mixing of the final ceramic powder; while adding the binder after the ceramic powder is fully mixed, the binder can be more evenly distributed on the surface of the ceramic particles, which is beneficial to the combination of the particles in the subsequent molding process.

[0053] In the present invention, the particle size of the solid particles in the slurry is preferably ≤0.2 μm.

[0054] After obtaining the slurry, the present invention spray-dries the slurry to obtain powder.

[0055] In the present invention, the inlet temperature of the spray drying is preferably 210-240° C., more preferably 220-230° C.; the outlet temperature is preferably 100-120° C., more preferably 100-110° C. The present invention has no particular limitation on the spray drying process, and the process known to those skilled in the art can be used.

[0056] In the present invention, by precisely controlling the outlet temperature and the inlet temperature, the main effects include: (1) A higher inlet air temperature accelerates the drying rate of the material. However, it is to avoid that the inlet air temperature is too high, which causes the surface of the material to be over-dried, forms a hard shell, and hinders the further evaporation of the internal moisture, thereby reducing the overall drying efficiency. If the inlet air temperature is too low, the material is not fully dried, and the water content of the product may be too high, affecting the storage stability and performance of the product. (2) The feed is controlled by the inlet air temperature, thereby controlling the size and shape of the particles. (3) When the outlet air temperature is high, the surface hardness of the obtained particles is larger and not easy to break, which is conducive to storage and transportation. However, if the outlet air temperature is too high, the moisture inside the particles cannot be discharged in time, forming hollow particles or particles containing bubbles inside. These particles may have quality problems in the subsequent use process, such as reduced strength and poor dispersibility. (4) The outlet air temperature also affects energy consumption. The higher the outlet air temperature, the more heat the hot air takes away, and the greater the energy consumption. Therefore, under the premise of ensuring the dryness of the material, the outlet air temperature should be reduced as much as possible to reduce energy consumption. In summary, the inlet and outlet air temperatures play a vital role in the spray granulation process. In actual production, the inlet and outlet air temperatures should be reasonably adjusted according to factors such as the properties of the material, product requirements and equipment performance to obtain high-quality granule products and reduce energy consumption.

[0057] In the present invention, the particle size of the powder is preferably 30 to 60 μm, more preferably 35 to 55 μm, and more preferably 40 to 50 μm. In the present invention, if the particle size is too large, it is easy to cause poor fluidity of the spherical powder, uneven filling of the green body during molding, and affect sintering densification. If the particle size is too small, the spherical powder is easy to agglomerate, affecting the fluidity during the pressing process, and also affecting the filling of the green body during molding, and ultimately affecting densification.

[0058] After obtaining the powder, the present invention sequentially performs a first pressing and a second pressing on the powder to obtain a ceramic green body.

[0059] In the present invention, the pressure of the first pressing is preferably 20-70MPa, specifically 20MPa, 30MPa, 40MPa, 50MPa, 60MPa, 70MPa; the holding time is 2-5min, specifically 2min, 3min, 4min, 5min; the first pressing is preferably performed in a hydraulic press. In the present invention, the functions of the first pressing mainly include: (1) Preliminary forming: The hydraulic process can apply a certain pressure to the spherical powder to initially form the desired shape. At this stage, the loose spherical powder can be quickly pressed into a relatively dense green body, laying the foundation for the subsequent cold isostatic pressing to further improve the density and uniformity. (2) Expelling some gas: During the hydraulic process, the pressure can cause some of the gas in the ceramic powder to be discharged, reducing the porosity in the green body. Although the gas cannot be completely eliminated, it can create better conditions for cold isostatic pressing.

[0060] In the present invention, the pressure of the second pressing is preferably 200-300MPa, specifically 200MPa, 220MPa, 240MPa, 260MPa, 280MPa, 300MPa. The holding time is preferably 5-15min, specifically 5min, 8min, 10min, 12min, 15min; the second pressing is preferably performed in a cold isostatic press. In the present invention, the effects of the second pressing mainly include: (1) Improving density uniformity: cold isostatic pressing can make the density of the ceramic material more uniform by applying uniform high pressure in all directions to the green body. Compared with hydraulic pressure, the pressure of cold isostatic pressing acts more evenly in all directions of the green body, which can effectively eliminate the density difference inside the green body and improve the quality of the product. (2) Enhancing the strength of the green body: cold isostatic pressing can significantly improve the strength of the green body. Under the action of high pressure, the ceramic particles are more tightly bonded and the structure of the green body is more stable, thereby enhancing the green body's strength properties such as compression resistance and bending resistance, which is beneficial to subsequent processing and treatment. (3) Improvement of microstructure: Cold isostatic pressing can make the microstructure of ceramic materials more compact and uniform. High pressure can induce plastic deformation and rearrangement of ceramic particles, reduce the pores and defects between particles, and thus improve the performance of the material (it can improve the hardness, wear resistance, corrosion resistance, etc. of ceramics).

[0061] After obtaining the ceramic green body, the present invention sequentially performs a first sintering, a second sintering and a third sintering on the ceramic green body to obtain the tin oxide ceramic material.

[0062] In the present invention, the temperature of the first sintering is preferably 500-700°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, the heating rate from room temperature to the first sintering temperature is preferably 2-4°C / min, and the holding time is preferably 2-4h. In the present invention, the effects of the first sintering mainly include: (1) particle rearrangement: the powder particles are in a relatively loose stacking state after molding. As the temperature rises, the particles begin to move and rearrange, so that the contact points between the particles increase and the contact area increases, creating conditions for subsequent material transfer and sintering reactions. (2) Reducing microcracks: allowing organic matter to be evenly and slowly removed from the green body, reducing microcracks caused by stress concentration. (3) Improving the air permeability of the green body to ensure smooth sintering: as the organic matter is gradually removed, the pore structure of the ceramic green body changes, and the air permeability is improved, which is conducive to the discharge of gas and the transfer of heat during the sintering process, making the sintering process more uniform and sufficient, and improving the sintering quality of the ceramic. (4) More thorough degreasing to maintain the shape and dimensional accuracy of the green body: The volatilization of organic matter during sintering will cause drastic volume changes in the green body, thereby affecting the shape and dimensional accuracy of the green body. After thorough degreasing, the volume and size changes of the green body are relatively small, and the shape and dimensional accuracy after molding can be better maintained. (5) Improve the density of ceramics: If the organic matter is not completely removed before sintering, it will decompose and volatilize during high-temperature sintering, producing a large amount of gas. If these gases cannot be discharged in time, pores will form in the ceramic green body, reducing the density and mechanical properties of the ceramic.

[0063] In the present invention, the temperature of the second sintering is preferably 900-1100°C, specifically 900°C, 950°C, 1000°C, 1050°C, 1100°C; the heating rate from the temperature of the first sintering to the temperature of the second sintering is preferably 2-4°C / min, and the holding time is preferably 2-10h, specifically 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h. In the present invention, the effects of the second sintering mainly include: (1) Forming a neck: The atoms at the contact point between the particles move to the contact point through diffusion, resulting in an increase in the material at the contact point, forming a so-called "neck" structure, just like a "neck" connecting two particles. This is an important sign of the beginning of sintering. The formation of the neck gives the particles a preliminary bonding force, but the overall green body is still relatively loose, and the density increase is not obvious. (2) Neck growth: As the temperature continues to rise, the atomic diffusion rate accelerates, the necks between the particles continue to grow, the connection between the particles becomes tighter, and the density of the green body gradually increases. This stage is the key stage of green body densification and has an important influence on the density and performance of the final ceramic product.

[0064] In the present invention, the temperature of the third sintering is preferably 1300-1600°C, specifically 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C, 1600°C; the heating rate from the temperature of the second sintering to the temperature of the third sintering is preferably 2-4°C / min, and the holding time is preferably 12-48h, specifically 12h, 18h, 24h, 30h, 36h, 42h, 48h. In the present invention, the effects of the third sintering mainly include: (1) Pore elimination: the material on the grain boundary continuously diffuses into the pores, so that the pores are gradually filled and eliminated, and the density of the green body is further improved, approaching the theoretical density. At this time, most of the pores have been separated into isolated small pores, and the size of these small pores continues to decrease until they finally disappear, making the ceramic material more dense. (2) Grain growth: under the action of high temperature, the grains will continue to grow, and the size and morphology of the grains will affect the properties of the ceramic. Generally speaking, ceramic materials with moderate grain size have good mechanical and physical properties, but if the grains grow excessively, it may lead to problems such as decreased strength and toughness of the ceramics. (3) Stable performance: After the late sintering process, the structure and performance of the ceramic material gradually become stable, and performance indicators such as strength, hardness, and density reach a high level, providing a good foundation for the subsequent processing and use of ceramic products.

[0065] In the present invention, the second sintering and the third sintering are preferably performed under oxygen conditions, that is, oxygen is introduced into the system starting from the second sintering.

[0066] In the present invention, sintering without oxygen introduction causes more significant high-temperature decomposition of tin oxide, resulting in pores in the ceramic material produced by decomposition. Introduction of oxygen can reduce the decomposition of tin oxide, reduce the porosity, and thus increase the relative density of the ceramic material.

[0067] In the present invention, the first sintering, the second sintering and the third sintering are preferably all pressureless sintering.

[0068] In the present invention, after the third sintering, it is also preferred to cool the obtained sintering material to room temperature, and the cooling rate is preferably 1-2°C / min. In the present invention, by limiting the cooling rate, it has the following effects: 1. Reducing thermal stress: During the sintering process, the temperature distribution inside the ceramic is uneven, and rapid cooling will cause inconsistent shrinkage of various parts of the ceramic, thereby generating large thermal stress. This thermal stress may cause defects such as cracks, deformation, and even rupture in the ceramic. Cooling under limited conditions can allow the temperature inside the ceramic to gradually become uniform in enough time, making the contraction of each part more synchronized, thereby reducing thermal stress and ensuring the integrity of the ceramic. 2. Improving density: In the later stage of sintering, there are still some tiny pores and defects inside the ceramic. In the process of cooling under limited conditions, the diffusion and migration of substances are still continuing, and these tiny pores and defects can be further filled and repaired, thereby improving the density of the ceramic.

[0069] The present invention also provides a tin oxide ceramic material prepared by the preparation method described in the above technical solution, wherein the relative density of the tin oxide ceramic material is 98.1-99.5% (based on the theoretical density of tin oxide of 6.95 g / cm 3 For reference), the volume resistivity is 28 to 61 mΩ·cm, and the average grain size is 1 to 5 μm.

[0070] The present invention also provides the use of the tin oxide ceramic material described in the above technical solution as a target material.

[0071] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0072] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0073] Example 1

[0074] 95g of tin oxide, 2.5g of tantalum pentoxide, 1g of zinc oxide, and 1.5g of gallium oxide were mixed, and evenly dispersed with 2g of polyethylene glycol and 0.1g of polydimethylsiloxane in 100g of pure water, and then put into a ball mill together with zirconium oxide grinding balls for wet ball milling; the ball mill speed was 300rpm, and the diameters of the zirconium oxide grinding balls were The mass ratio of the three kinds of balls is 1:3:6; the ball-to-material ratio is 2:1, and the ball milling time is 12 hours; then 2g of polyvinyl alcohol is added and the ball milling is continued for 0.5 hours to obtain a slurry;

[0075] The slurry is spray-dried to obtain a powder with a particle size of 40 μm, wherein the spray drying air inlet temperature is 220° C. and the air outlet temperature is 105° C.;

[0076] The powder is first pressed by a hydraulic press at a pressure of 50 MPa for 2 min; then the powder is secondly pressed by a cold isostatic press at a pressure of 280 MPa for 8 min to obtain a ceramic blank;

[0077] The ceramic blank was sintered by atmospheric pressure sintering technology, firstly, the temperature was raised from room temperature to 600°C at a heating rate of 3°C / min and kept at this temperature for 3 hours; then, the temperature was raised to 1050°C at a heating rate of 3°C / min, oxygen was introduced and kept at this temperature for 8 hours; then, the temperature was continued to be raised at a heating rate of 1°C / min to 1450°C and kept at this temperature for 24 hours; after the sintering was completed, the temperature was slowly lowered to room temperature at a cooling rate of 2°C / min, and a tin oxide ceramic material with a relative density of 98.1%, a volume resistivity of 28mΩ·cm and an average grain size of 2μm was obtained.

[0078] Example 2

[0079] 95.5 g of tin oxide, 2.5 g of antimony pentoxide, 1 g of manganese dioxide, and 1 g of gallium oxide were mixed, and evenly dispersed with 2 g of polyethylene glycol and 0.1 g of polydimethylsiloxane in 100 g of pure water, and then put into a ball mill together with zirconium oxide grinding balls for wet ball milling; the ball mill speed was 300 rpm, and the diameters of the zirconium oxide grinding balls were The mass ratio of the three kinds of balls is 1:3:6; the ball-to-material ratio is 2:1, and the ball milling time is 20 hours; then 2g of polyvinyl alcohol is added and the ball milling is continued for 0.5 hours to obtain a slurry;

[0080] The slurry is spray-dried to obtain a powder with a particle size of 45 μm, wherein the spray drying air inlet temperature is 230° C. and the air outlet temperature is 105° C.;

[0081] The powder is first pressed into shape by a hydraulic press at a pressure of 50 MPa and a holding time of 2 min; and then the powder is secondly pressed by a cold isostatic press at a pressure of 260 MPa and a holding time of 12 min to obtain a ceramic green body;

[0082] The tin oxide ceramic blank was sintered by atmospheric pressure sintering technology, firstly, the temperature was increased from room temperature to 600°C at a heating rate of 3°C / min and kept at this temperature for 3 hours; then, the temperature was increased to 1050°C at a heating rate of 3°C / min, oxygen was introduced and kept at this temperature for 8 hours; then, the temperature was increased at a heating rate of 1°C / min until it reached 1500°C and kept at this temperature for 24 hours; after the sintering was completed, the temperature was slowly cooled to room temperature at a cooling rate of 2°C / min, and a tin oxide ceramic material with a relative density of 98.7%, a volume resistivity of 61mΩ·cm and an average grain size of 5μm was obtained.

[0083] Example 3

[0084] 93g of tin oxide, 4g of tungsten trioxide, 1.5g of copper oxide, and 1.5g of gallium oxide were mixed, and evenly dispersed with 1.5g of polyethylene glycol and 0.1g of polydimethylsiloxane in 100g of pure water, and then put into a ball mill together with zirconium oxide grinding balls for wet ball milling; the ball mill speed was 300rpm, and the diameters of the zirconium oxide grinding balls were The mass ratio of the three kinds of balls is 1:3:6; the ball-to-material ratio is 2:1, and the ball milling time is 24 hours; then 2g of polyvinyl alcohol is added and the ball milling is continued for 0.5 hours to obtain a slurry;

[0085] The slurry is spray-dried to obtain a powder with a particle size of 50 μm, wherein the spray drying air inlet temperature is 240° C. and the air outlet temperature is 105° C.;

[0086] The powder is first pressed by a hydraulic press at a pressure of 50 MPa for 2 min; then the powder is secondly pressed by a cold isostatic press at a pressure of 240 MPa for 15 min to obtain a ceramic blank;

[0087] The tin oxide ceramic blank was sintered by atmospheric pressure sintering technology, firstly, the temperature was increased from room temperature to 600°C at a heating rate of 3°C / min and kept at this temperature for 3 hours; then, the temperature was increased to 1050°C at a heating rate of 3°C / min, oxygen was introduced and kept at this temperature for 8 hours; then, the temperature was increased at a heating rate of 1°C / min until it reached 1550°C and kept at this temperature for 18 hours; after the sintering was completed, the temperature was slowly lowered to room temperature at a cooling rate of 2°C / min, and a tin oxide ceramic material with a relative density of 99.5%, a volume resistivity of 33mΩ·cm and an average grain size of 3μm was obtained.

[0088] Example 4

[0089] 93.6 g of tin oxide, 4 g of molybdenum trioxide, 1.2 g of zinc oxide, and 1.2 g of gallium oxide were mixed, and evenly dispersed with 1.5 g of polyethylene glycol and 0.1 g of polydimethylsiloxane in 100 g of pure water, and then put into a ball mill together with zirconium oxide grinding balls for wet ball milling; the ball mill speed was 300 rpm, and the diameters of the zirconium oxide grinding balls were The mass ratio of the three kinds of balls is 1:3:6; the ball-to-material ratio is 2:1, and the ball milling time is 12 hours; then 2g of polyvinyl alcohol is added and the ball milling is continued for 0.5 hours to obtain a slurry;

[0090] The slurry is spray-dried to obtain a powder with a particle size of 45 μm, wherein the spray drying air inlet temperature is 230° C. and the air outlet temperature is 105° C.;

[0091] The powder is first pressed by a hydraulic press at a pressure of 50 MPa for 2 min; then the powder is secondly pressed by a cold isostatic press at a pressure of 255 MPa for 12 min to obtain a ceramic blank;

[0092] The tin oxide ceramic blank was sintered by atmospheric pressure sintering technology, firstly, the temperature was increased from room temperature to 600°C at a heating rate of 3°C / min and kept at this temperature for 3 hours; then, the temperature was increased to 1050°C at a heating rate of 3°C / min, oxygen was introduced and kept at this temperature for 8 hours; then, the temperature was increased at a heating rate of 1°C / min until it reached 1350°C and kept at this temperature for 28 hours; after the sintering was completed, the temperature was slowly lowered to room temperature at a cooling rate of 2°C / min, and a tin oxide ceramic material with a relative density of 98.5%, a volume resistivity of 51mΩ·cm and an average grain size of 3μm was obtained.

[0093] Example 5

[0094] 94.5 g of tin oxide, 3 g of vanadium pentoxide, 1.5 g of copper oxide, and 1.0 g of gallium oxide were mixed, and evenly dispersed with 1.5 g of polyethylene glycol and 0.1 g of polydimethylsiloxane in 100 g of pure water, and then put into a ball mill together with zirconium oxide grinding balls for wet ball milling; the ball mill speed was 300 rpm, and the diameters of the zirconium oxide grinding balls were The mass ratio of the three kinds of balls is 1:3:6; the ball-to-material ratio is 2:1, and the ball milling time is 8 hours; then 2g of polyvinyl alcohol is added and the ball milling is continued for 0.5 hours to obtain a slurry;

[0095] The slurry is spray-dried to obtain a powder with a particle size of 53 μm, wherein the spray drying air inlet temperature is 245° C. and the air outlet temperature is 105° C.;

[0096] The powder is first pressed by a hydraulic press at a pressure of 50 MPa for 2 min; then the powder is secondly pressed by a cold isostatic press at a pressure of 255 MPa for 12 min to obtain a ceramic blank;

[0097] The tin oxide ceramic blank was sintered by atmospheric pressure sintering technology, firstly, the temperature was increased from room temperature to 600°C at a heating rate of 3°C / min and kept at this temperature for 3 hours; then, the temperature was increased to 1050°C at a heating rate of 3°C / min, oxygen was introduced and kept at this temperature for 8 hours; then, the temperature was continued to be increased at a heating rate of 1°C / min to 1400°C and kept at this temperature for 24 hours; after the sintering was completed, the temperature was slowly cooled to room temperature at a cooling rate of 2°C / min, and a tin oxide ceramic material with a relative density of 98.8%, a volume resistivity of 38mΩ·cm and an average grain size of 4μm was obtained.

[0098] Comparative Example 1

[0099] A tin oxide ceramic material was prepared in the manner of Example 1, except that no gallium oxide was added.

[0100] Comparative Example 2

[0101] A tin oxide ceramic material was prepared in the manner of Example 1, except that 3 g of gallium oxide was added.

[0102] Comparative Example 3

[0103] A tin oxide ceramic material was prepared in the manner of Example 1, except that no oxygen was introduced when the temperature was raised to 1050°C.

[0104] Comparative Example 4

[0105] A tin oxide ceramic material was prepared in the manner of Example 1, except that the second pressing was not performed.

[0106] Comparative Example 5

[0107] The tin oxide ceramic material was prepared in the manner of Example 1, except that multiple sintering was not performed. The specific sintering process was: heating from room temperature to 1450° C. at a heating rate of 3° C. / min and keeping the temperature for 24 hours.

[0108] Performance Testing

[0109] Test Example 1

[0110] Figure 1 is a cross-sectional SEM image of the tin oxide ceramic material obtained in Example 1; Figure 1 It can be seen that the grain size of the tin oxide ceramic target obtained in Example 1 is small and uniform, and the scale in the figure is 1.889 μm;

[0111] Figure 2 The XRD patterns of the tin oxide raw material and the obtained tin oxide ceramic material in Example 1 are as follows: Figure 2 It can be seen that after being doped with other oxides, the obtained tin oxide ceramic material still has only SnO2 phase, which is more conducive to achieving stable sputtering when used in sputtering.

[0112] Test Example 2

[0113] The tin oxide ceramic materials obtained in Examples 1 to 5 and Comparative Examples 1 to 5 were subjected to performance tests, and the test results obtained are shown in Table 1;

[0114] Table 1 Properties of tin oxide ceramic materials obtained in Examples 1 to 5 and Comparative Examples 1 to 5

[0115]

[0116] Among them, the bending strength is tested according to the GB / T-6569-2006 test standard.

[0117] As can be seen from Table 1, the tin oxide ceramic material obtained by the present invention has high relative density, low resistivity and fine grain size. Among them, the three components in the tin oxide ceramic target are indispensable. The conductive doped oxide greatly improves the conductivity of tin oxide by introducing oxygen vacancies; the sintering aid greatly promotes the particle rearrangement and mass transfer process by forming a suitable liquid phase, and promotes the sintering densification of tin oxide; gallium oxide hinders the growth of grains by pinning at the grain boundaries, which is conducive to the formation of a target with fine and uniform grains.

[0118] Application Examples

[0119] The tin oxide ceramic material obtained in Example 1 was used as a target material for magnetron sputtering. The magnetron sputtering conditions were: DC sputtering, the substrate was alkali-free glass, and the vacuum degree of the chamber was less than 6×10 -4 Pa, sputtering power 150 W, sputtering pressure 0.6 Pa, oxygen-argon ratio 1:10, sputtering temperature is room temperature, and sputtering time is 6 min.

[0120] The film thickness tester measured the thickness of the prepared tin oxide film to be 105nm, and the sputtering rate was calculated to be 17.5nm / min; the UV spectrophotometer tested the transmittance of the prepared tin oxide film, and the average transmittance in the range of 380-1400nm was 85.2%; the Hall effect instrument measured the electron mobility of the prepared tin oxide film to be 31cm2 / V·s; this shows that the prepared tin oxide film has good light transmittance and high electron mobility, and the sputtering rate is fast because of the small grain size of the target material.

[0121] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a tin oxide ceramic material, characterized in that: The following steps are involved: Mixing solid raw materials, dispersants, defoamers and binders, and performing wet ball milling to obtain slurry; the solid raw materials include tin oxide, conductive doped oxides, sintering aids and gallium oxide; The slurry is spray-dried to obtain a powder; The powder is subjected to a first pressing and a second pressing in sequence to obtain a ceramic green body; The ceramic green body is subjected to a first sintering, a second sintering and a third sintering in sequence to obtain the tin oxide ceramic material.

2. The preparation method according to claim 1, characterized in that: The conductive doped oxide includes one or more of tantalum pentoxide, antimony trioxide, tungsten trioxide, molybdenum trioxide and vanadium pentoxide; The sintering aid includes one or more of zinc oxide, copper oxide, silicon dioxide and manganese dioxide; The mass ratio of the tin oxide to the conductive doped oxide is 91-99:0.5-4; The mass ratio of tin oxide to sintering aid is 91-99:0.25-3; The mass ratio of tin oxide to gallium oxide is 91-99:0.25-2.

3. The preparation method according to claim 1, characterized in that: The dispersant includes one or more of polyacrylamide, styrene-maleic anhydride copolymer, polyethylene glycol, polyvinyl pyrrolidone, triethylhexyl phosphoric acid, sodium lauryl sulfate, methyl amyl alcohol and cellulose derivatives; the cellulose derivatives include hydroxypropyl methylcellulose and / or carboxymethyl cellulose; The defoaming agent includes one or more of polydimethylsiloxane, ethylene oxide-propylene oxide copolymer, diethylhexanol, isooctyl alcohol, isopentanol, diisobutyl carbinol, distearyl ethylenediamine and tributyl phosphate; The binder includes one or more of cellulose, polyvinyl alcohol, polyvinyl acetate, polyvinyl ketone and polyacrylic acid.

4. The preparation method according to claim 1 or 3, characterized in that: The mass of the dispersant is 0.5-2% of the mass of the solid raw material; The mass of the defoamer is 0.05-0.1% of the mass of the solid raw material; The mass of the binder is 1-4% of the mass of the solid raw material.

5. The preparation method according to claim 1, characterized in that: The dispersion medium used in the wet ball milling is water, and the mass of the water is 70-100% of the mass of the solid raw material; The rotation speed of the wet ball mill is 150-350 rpm; The grinding balls used in the wet ball mill are zirconia grinding balls, which include grinding balls with a diameter of 6 mm, grinding balls with a diameter of 4 mm, and grinding balls with a diameter of 2 mm, and the mass ratio of the grinding balls with a diameter of 6 mm, the grinding balls with a diameter of 4 mm, and the grinding balls with a diameter of 2 mm is 1:3:6; The ball-to-material ratio of the wet ball milling is 1 to 6:

1.

6. The preparation method according to claim 1, characterized in that: The inlet temperature of the spray drying is 210-240°C, and the outlet temperature is 100-120°C.

7. The preparation method according to claim 1, characterized in that: The first pressing pressure is 20-70 MPa, and the holding time is 2-5 min; The second pressing pressure is 200-300 MPa, and the holding time is 5-15 min.

8. The preparation method according to claim 1, characterized in that: The first sintering temperature is 500-700°C, and the holding time is 2-4h; The second sintering temperature is 900-1100°C, and the holding time is 2-10h; The temperature of the third sintering is 1300-1600° C., and the holding time is 12-48 hours; The second sintering and the third sintering are both performed under oxygen conditions.

9. The tin oxide ceramic material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The relative density of the tin oxide ceramic material is 98.1-99.5%, the volume resistivity is 28-61 mΩ·cm, and the average grain size is 1-5 μm.

10. Use of the tin oxide ceramic material according to claim 9 as a target material.

Citation Information

Patent Citations

  • Manufacturing of silicon dioxide aerogel powder body and glass binding agent composite thermal insulation material

    CN104556967A

  • Gallium oxide doped tin oxide ceramic target material and preparation method thereof

    CN112723875A

  • Method for preparing dense layer useful as electrode and / or electrolyte of lithium ion battery and lithium ion microbattery obtained thereby

    CN115699345A

  • Tin oxide-based evaporation target material as well as preparation method and application thereof

    CN117865670A

  • Preparation method of tin oxide target material with good conductivity

    CN118063205A

Cited By

  • Preparation method of cerium, tantalum and zinc co-doped tin oxide target material

    CN120025164A